The I-KAPCAM-AI-Q: a novel instrument for evaluating health care providers’ AI awareness in Italy - Cofini, Vincenza; Piccardi, Laura; Benvenuti, Eugenio; Di Pangrazio, Ginevra; Cimino, Eleonora; Mancinelli, Martina; Muselli, Mario; Petrucci, Emiliano; Picchi, Giovanna; Palermo, Patrizia; Tobia, Loreta; Barbonetti, Arcangelo; et al. (Frontiers in Public Health, 2025)
BackgroundUnderstanding healthcare providers’ readiness and attitudes is crucial for integrating AI in healthcare, yet no validated tool exists to evaluate these aspects among Italian physicians. This study developed and validated the Italian Knowledge, Attitudes, Practice, and Clinical Agreement between Medical Doctors and the Artificial Intelligence Questionnaire (I-KAPCAM-AI-Q).MethodsThis was a cross-sectional validation study. The validation process included expert review (n = 18), face validity assessment (n = 20), technical implementation testing, and pilot testing (n = 203) with both residents and specialists. The questionnaire contained 29 items, one clinical universal scenario, and 6 clinical scenarios specific to 6 specialists.ResultsThe questionnaire demonstrated strong content validity (S-CVI/Ave = 0.98) and acceptable internal consistency (Cronbach’s Alpha = 0.7481, KR-21 = 0.832). Pilot testing revealed only 17% of participants had received digital technology training during medical education, while 91% showed clinical agreement with AI-proposed diagnoses. Knowledge in diagnostics was highest among AI applications (48%). Residents showed higher interest in technical support (58.3% vs. 42.0%, p = 0.021) and evidence-based validation (61.2% vs. 47.0%, p = 0.043) compared to specialists.ConclusionThe I-KAPCAM-AI-Q provides a reliable tool for assessing healthcare providers’ AI readiness and highlights the need for enhanced digital health education in medical curricula.